2006
DOI: 10.1007/s00445-005-0034-5
|View full text |Cite
|
Sign up to set email alerts
|

Pahoehoe flows from the central Paraná Continental Flood Basalts

Abstract: Inflated and compound pahoehoe flows have been identified within the central Paraná Continental Flood Basalts based upon their morphology, surface features, and internal zonation. Pahoehoe flow features have been studied at five localities in the western portion of Paraná State, Brazil: Ponte Queimada, Toledo, Rio Quitéria, Matelândia and Cascavel. We have interpreted the newly recognized flow features using concepts of Hawaiian pahoehoe formation and emplacement that have been previously applied to the Columb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
19

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 45 publications
0
32
0
19
Order By: Relevance
“…The previous studies concerning facies architecture and geochemistry characterization of the volcanic rocks in the Southern portion of SGF have assumed an effusive nature for the acidic units (Umann et al 2001;Waichel et al 2006;Simões & Lima 2011;Rossetti 2011;Lima et al 2012;Polo & Janasi 2014). In the present work, three profiles of volcanic rocks exposure were investigated.…”
Section: Discussionmentioning
confidence: 92%
“…The previous studies concerning facies architecture and geochemistry characterization of the volcanic rocks in the Southern portion of SGF have assumed an effusive nature for the acidic units (Umann et al 2001;Waichel et al 2006;Simões & Lima 2011;Rossetti 2011;Lima et al 2012;Polo & Janasi 2014). In the present work, three profiles of volcanic rocks exposure were investigated.…”
Section: Discussionmentioning
confidence: 92%
“…The Gramado type low-Ti basalts correspond to the early PMP volcanic manifestations, and overlay eolian sandstones of the Paraná Basin in the southern portion of the province (Waichel et al, 2006. They were followed by the Esmeralda type basalts, which exhibit, towards the top, intercalations with silicic volcanic rocks of the low-Ti Palmas type (dacites and rhyolites; Bellieni et al, 1986;Garland et al, 1995;Nardy, 1995;Nardy et al, 2008;Waichel et al, 2012).…”
Section: Stratigraphymentioning
confidence: 99%
“…These studies supplied the basis for the stratigraphic organization and identification of the facies architecture in these provinces (Bondre et al 2004, Jerram 2002, Jerram & Widdowson 2005, Waichel et al 2012. Several studies have indicated that the spreading of these immense volumes of continental basalts was similar to that of the Hawaiian pahoehoe-type flows (Hon et al 1994, Kent et al 1998, Bondre et al 2004, Sheth 2006, Waichel et al 2006.…”
Section: Characterization Of Subaerial Basic Flowsmentioning
confidence: 99%